Radioguided surgery with β radiation: a novel application with Ga68. Issue 1 (December 2018) - Collamati, Francesco; Bocci, Valerio; Castellucci, Paolo; De Simoni, Micol; Fanti, Stefano; Faccini, Riccardo; Giordano, Alessandro; Maccora, Daria; Mancini-Terracciano, Carlo; Marafini, Michela; Mirabelli, Riccardo; Morganti, Silvio; et al.
Abstract Radio Guided Surgery is a technique helping the surgeon in the resection of tumors: a radiolabeled tracer is administered to the patient before surgery and then the surgeon evaluates the completeness of the resection with a handheld detector sensitive to emitted radiation. Established methods rely onγ emitting tracers coupled withγ detecting probes. The efficacy of this technique is however hindered by the high penetration ofγ radiation, limiting its applicability to low background conditions. To overtake such limitations, a novel approach to RGS has been proposed, relying onβ − emitting isotopes together with a dedicatedβ probe. This technique has been proved to be effective in firstex -vivo trials. We discuss in this paper the possibility to extend its application cases to68 Ga, aβ + emitting isotope widely used today in nuclear medicine. To this aim, a retrospective study on 45 prostatic cancer patients was performed, analysing their68 Ga-PSMA PET images to asses if the molecule uptake is enough to apply this technique. Despite the expected variability both in terms of SUV (median 4.1, IQR 3.0–6.1) and TNR (median 9.4, IQR 5.2–14.6), the majority of cases have been found to be compatible withβ -RGS with reasonable injected activity and probing time (5 s).